PENGARUH KREDIT USAHA RAKYAT (KUR) TERHADAP JUMLAH TENAGA KERJA PADA UMKM DI KOTA PALU (Sebuah Pendekatan Analisis Jalur) - Asrianti, Asrianti; Antara, Made; Effendy, Effendy (AGROTEKBIS, 2018)
The general aim of the research was to determine the influence of business credit on the number of labor at micro, small and medium enterprises (SMEs) in Palu City and the particular aim was to determine the direct influence of capacity, capital and conditions of SMEson thesum ofbusiness credit and the number of labors.  The research was conducted in Palu city on December 2016 until January 2017. The analysis tool used is path analysis. The results showed that such variablesas capacity, capital and conditions directly influenced the sum of business creditsignificantly while their influence was not significant on the number of labors except for the capital. The capacity, condition, and the sum of credit directly affected the number of labors significantly.